日米で食薬区分の異なるメラトニンのインターネットを介した個人輸入における安全性情報の比較 - 小林, 真一; 大塚, 邦子; 内田, 直樹; 野村, 靖幸; 安原, 一 (社会薬学, 2014)
Classification of food and pharmaceutical products are different. In the proper use of pharmaceutical products, it is essential for a medical consumer to receive the drug information about effectiveness, safety and quality of it. On the other hand, since legal classification between medicines and dietary supplements was based their cultures, the classification of each drug is different in each country. Melatonin is a hormone produced by the pineal gland and used for improvement of the jet lag. We searched melatonin product information of Japan and the United States by using Internet search mainly and investigated the relationship between amount of product information and product classification. Melatonin is classified as a dietary supplement in the United States, the product information of efficacy and safety is displayed as “Supplement Facts” and the use of melatonin in children is not recommended. On the other hand, melatonin is classified as a pharmaceutical product in Japan, but is not produced in Japan. Therefore, it is difficult to have it for Japanese customers, and then they personally import using the Internet with their self-responsibility. However it is difficult to obtain its appropriate information for consumers, because of the regulation of the Pharmaceutical Affairs Law. It has been reported that the poisoning accident by the excessive intake of melatonin already. It will increase the risk of the health problem to purchase melatonin through the Internet more. Therefore, we concluded that Internet purchase of Medicines had a high risk for Japanese customers since there was not sufficient drug information.